2010
DOI: 10.1590/s0066-782x2010005000071
|View full text |Cite
|
Sign up to set email alerts
|

Morbimortalidade em octogenários submetidos à cirurgia de revascularização miocárdica

Abstract: Background: Given the progressive increase in longevity and the need of an increasingly elderly population to undergo myocardial revascularization surgery (MRS), it becomes necessary to know its risks and benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As a consequence of older patient referral for cardiac surgery, cardiac pathology is often more considerable. Indeed, we found 36.3% of octogenarians received combined cardiac procedures (predominantly AVR and CABG), which is among the highest rates compared to previous studies [ 10 ]-[ 12 ] and associated with longer CPB and aortic cross clamp time. It is not surprising that octogenarians with more complex procedures have higher risk for major post-operative complications and consequently greater health service utilization (i.e.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As a consequence of older patient referral for cardiac surgery, cardiac pathology is often more considerable. Indeed, we found 36.3% of octogenarians received combined cardiac procedures (predominantly AVR and CABG), which is among the highest rates compared to previous studies [ 10 ]-[ 12 ] and associated with longer CPB and aortic cross clamp time. It is not surprising that octogenarians with more complex procedures have higher risk for major post-operative complications and consequently greater health service utilization (i.e.…”
Section: Discussionmentioning
confidence: 61%
“…Operating on this specific demographic is not only a challenge to cardiac surgeons but also a challenge to cardiologists, anesthesiologists, CVICU intensivists, and the whole medical system [ 11 ]. Previous studies have shown that the in-hospital mortality in octogenarians undergoing isolated CABG, AVR and MVR were 6.8%-14.3% [ 5 ],[ 12 ]-[ 14 ], 4.5%-12.6% [ 6 ],[ 15 ]-[ 17 ], and 2.7%-18.5% [ 7 ],[ 18 ], respectively. In a multi-center retrospective study gathering data from 22 high volume cardiac centers in the United States, the reported in-hospital mortality rates for octogenarians after cardiac surgery were 8.1% for isolated CABG, 10.1% for combined CABG and AVR, and 19.6% for combined CABG and MVR [ 19 ].…”
Section: Discussionmentioning
confidence: 99%